Sulfide-based solid electrolyte and method for manufacturing the same

CN123018103APending Publication Date: 2026-10-30HYUNDAI MOTOR CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610526598.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-30
Filing Date
2026-04-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但是,硫化物系固体电解质存在如下问题:会与大气中的水分反应而产生有毒的硫化氢(H2S)气体,且在高电压下的氧化稳定性较差,高电压驱动时易与正极材料发生副反应

Benefits of technology

[0032]基于本发明的一实施例的固体电解质制造方法,能够制造与空气中的水分的反应性低且在高电压下的稳定性和离子电导率优异的固体电解质。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018103A_ABST
    Figure CN123018103A_ABST
Patent Text Reader

Abstract

The present invention relates to a sulfide-based solid electrolyte and a method for manufacturing the same, wherein the solid electrolyte according to an embodiment of the present invention can include a compound represented by the following Chemical Formula 1,[Chemical Formula 1]Li a‑nb M b PS c X d In the above Chemical Formula 1, M is one or more selected from transition metal elements having an ionic radius of 0.4 Å or more and 1.0 Å or less and a sulfur dissociation energy of 0.5 eV or more, n represents the oxidation number of the above M and is greater than 1, X is one or more selected from Group 17 of the periodic table, 6 ≤ a ≤ 8, 0 < b < 0.2, 3 ≤ c ≤ 6, 0 < d ≤ 3, and 5.2 ≤ a - nb ≤ 6.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to sulfide-based solid electrolytes and methods for manufacturing the same, and more specifically, to sulfide-based solid electrolytes in which lithium sites are replaced by specific elements and methods for manufacturing the same. Background Technology

[0002] In recent years, with the development of the electrical, electronics, communications, and computer industries, the market for environmentally friendly vehicles and energy storage has continued to grow, making the development of highly safe and low-cost lithium-ion secondary batteries extremely important. In particular, due to rising energy prices and environmental protection demands, the development of electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs) is actively underway. Therefore, there is an even greater need to develop lithium-ion secondary batteries with excellent lifespan and capacity performance, and low cost, sufficient for commercialization in these various vehicle types.

[0003] With the expansion of applications, lithium-ion batteries are being developed towards higher capacity, lower cost, higher safety, and larger surface area, with an increasingly urgent need to improve safety and performance. However, existing lithium-ion batteries, using liquid electrolytes, suffer from high risks of electrolyte leakage and fire; and with the increasing capacity and surface area of ​​batteries, safety issues are receiving more and more attention. Therefore, in recent years, research on all-solid-state lithium-ion batteries utilizing non-flammable inorganic solid electrolytes has been actively carried out to improve safety. Furthermore, all-solid-state lithium-ion batteries are attracting considerable attention as a next-generation battery with advantages such as safety, high energy density, and long lifespan.

[0004] Solid electrolytes can be divided into oxide-based solid electrolytes and sulfide-based solid electrolytes. Compared with oxide-based solid electrolytes, sulfide-based solid electrolytes have the advantages of high lithium-ion conductivity and stability over a wide voltage range. However, sulfide-based solid electrolytes have the following problems: they can react with moisture in the atmosphere to produce toxic hydrogen sulfide (H2S) gas, and they have poor oxidation stability at high voltages, making them prone to side reactions with the cathode material when driven by high voltage.

[0005] Existing technical documents Patent Document 1: US 10,446,872 B2 Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide a solid electrolyte with low reactivity with water and excellent ionic conductivity.

[0007] Another technical problem to be solved by the present invention is to provide a method for manufacturing a solid electrolyte, which can produce a solid electrolyte with low reactivity to moisture in the air and excellent stability and ionic conductivity under high voltage.

[0008] (1) The present invention provides a solid electrolyte comprising a compound represented by the following chemical formula 1.

[0009] [Chemical Formula 1] Li a-nb M b PS c X d In the above chemical formula 1, M is one or more transition metal elements selected from those with an ionic radius of 0.4 Å or more and 1.0 Å or less and a sulfur dissociation energy of 0.5 eV or more; n represents the oxidation number of M, which is greater than 1; X is one or more elements selected from group 17 of the periodic table, where 6 ≤ a ≤ 8, 0 < b < 0.2, 3 ≤ c ≤ 6, 0 < d ≤ 3, and 5.2 ≤ a - nb ≤ 6.

[0010] (2) In the solid electrolyte described in (1) above provided by the present invention, the solid electrolyte contains a compound represented by the following chemical formula 2.

[0011] [Chemical Formula 2] Li a-nb □ nb-b M b PS c X d In the above chemical formula 2, M is selected from one or more of Co, Ni, Nb, and Mg, □ is a lithium site vacancy, n represents the oxidation number of M and is greater than 1, X is selected from one or more elements of group 17 of the periodic table, 6≤a≤8, 0<b<0.2, 3≤c≤6, 0<d≤3, 5.2≤a-nb≤6, 0<nb-b≤2.8.

[0012] (3) In the solid electrolyte described in (1) or (2) above provided by the present invention, the solid electrolyte contains a compound represented by the following chemical formula 3.

[0013] [Chemical Formula 3] Li 5.5-nb □ nb-b M b PS 4.5 Cl c1 Br c2 In the above chemical formula 3, M is selected from one or more of Co, Ni, Nb, and Mg, □ represents a lithium site vacancy, n represents the oxidation number of M, and is greater than 1, 0.05≤b<0.2, 5.2≤5.5-nb≤6, 0<c1≤1, 0<c2≤1, 0<nb-b≤2.8.

[0014] (4) The solid electrolyte provided by the present invention according to any one of (1) to (3) above, wherein the solid electrolyte has a crystal structure belonging to space group F-43m.

[0015] (5) The solid electrolyte described in any one of (1) to (4) above provided by the present invention, wherein the solid electrolyte has an agyrodite crystal structure.

[0016] (6) The solid electrolyte described in any one of (1) to (5) above provided by the present invention has an a-axis lattice constant of 9.9 Å or less as calculated by Rietveld analysis.

[0017] (7) The solid electrolyte described in any one of (1) to (6) above provided by the present invention has an L value of 8 or more and 46 or less when measured with a HunterLab colorimeter.

[0018] (8) The solid electrolyte provided by the present invention, in any one of (1) to (7) above, does not have peaks at the positions of 2θ 27±0.5°, 36±0.5°, and 40±1° in the XRD pattern of the solid electrolyte measured by CuKα rays.

[0019] (9) The solid electrolyte provided by the present invention, in any one of (1) to (8) above, does not have peaks at the positions of 2θ 35±0.5° and 46±0.5° in the XRD pattern of the solid electrolyte measured by CuKα rays.

[0020] (10) The solid electrolyte described in any one of (1) to (9) above provided by the present invention has a resistance value of 7Ω or less calculated based on the impedance measured by EIS.

[0021] (11) The solid electrolyte provided by the present invention according to any one of (1) to (10) above, wherein the ionic conductivity of the solid electrolyte is 7 mS / cm or more.

[0022] (12) The peak intensity P1 observed at a position of 2θ = 25.5 ± 0.5° in the XRD pattern of the solid electrolyte provided by the present invention using CuKα rays and the peak intensity P2 observed at a position of 2θ = 25.5 ± 0.5° in the XRD pattern of the solid electrolyte using CuKα rays after the solid electrolyte has been exposed to a drying chamber with a dew point temperature of -60°C for 24 hours, is P1:P2 = 1:0.7 or more and 1:0.95 or less.

[0023] (13) The solid electrolyte provided by the present invention according to any one of (1) to (12) above has an ionic conductivity I1 measured for the solid electrolyte and an ionic conductivity I2 measured after the solid electrolyte has been exposed to a drying chamber at a dew point temperature of -60°C for 24 hours, with the ratio I1:I2 being 1:0.5 or more and 1:0.8 or less.

[0024] (14) The solid electrolyte described in any one of (1) to (13) above provided by the present invention, when 0.1g of the solid electrolyte is placed in an acrylic box of size 130mm×130mm×250mm, and the hydrogen sulfide generation is measured to be less than 310ppm after being exposed to the atmosphere at 65% humidity for 20 minutes using a Gas Tiger 6000 device.

[0025] (15) The present invention provides a method for manufacturing a solid electrolyte, comprising: a step (S1) of preparing lithium raw material, phosphorus sulfide raw material, transition metal raw material and halogen element raw material, and crushing and mixing them; and a step (S2) of calcining the product of the above step (S1) at a temperature range of 300°C or higher and 600°C or lower, wherein the transition metal raw material is any one or more metal compounds selected from transition metal elements with an ionic radius of 0.4 Å or higher and 1.0 Å or lower and a sulfur dissociation energy of 0.5 eV or higher.

[0026] (16) In the solid electrolyte manufacturing method described in (15) above provided by the present invention, the transition metal raw material is any one or more metal compounds selected from Co, Ni, Nb and Mg.

[0027] (17) In the solid electrolyte manufacturing method described in (15) or (16) above provided by the present invention, the transition metal raw material is any one or more divalent metal halides of Co, Ni, Nb and Mg.

[0028] (18) In the solid electrolyte manufacturing method of any one of (15) to (17) provided by the present invention, the above step (S2) is performed for more than 4 hours and less than 8 hours.

[0029] (19) In any one of (15) to (18) above provided by the present invention, the above step (S2) is performed in a calcining furnace filled with inert gas.

[0030] (20) The present invention provides an all-solid-state battery comprising a solid electrolyte according to any one of (1) to (14) above.

[0031] The solid electrolyte based on an embodiment of the present invention exhibits low reactivity with moisture in the air and excellent stability and ionic conductivity under high voltage.

[0032] A solid electrolyte manufacturing method based on an embodiment of the present invention can produce a solid electrolyte that exhibits low reactivity with moisture in the air and excellent stability and ionic conductivity under high voltage. Attached Figure Description

[0033] Figure 1 This is a schematic diagram illustrating the crystal structure of a conventional sulfide-based solid electrolyte.

[0034] Figure 2 This is a schematic diagram illustrating the crystal structure of a sulfide-based solid electrolyte based on an embodiment of the present invention.

[0035] Figure 3 This is a SEM-EDS image of a solid electrolyte based on Example 1 of the present invention.

[0036] Figure 4 This is a SEM-EDS image of the solid electrolyte of Comparative Example 1 based on the present invention.

[0037] Figure 5 and Figure 6 The XRD patterns are of the solid electrolytes of Examples 1 to 3 and Comparative Examples 1 to 3 of the present invention.

[0038] Figure 7 These are images taken of solid electrolytes based on Examples 1, 2, Comparative Examples 1 and 3 of the present invention.

[0039] Figure 8 These are impedance diagrams of the solid electrolytes of Examples 1 to 3 and Comparative Examples 2 to 4 of the present invention.

[0040] Figure 9 This is a specific capacity diagram of the solid electrolyte pressed powder molded cell of Embodiment 1 and Comparative Example 1 of the present invention for each cycle.

[0041] Figure 10The XRD patterns observed before and after exposing the solid electrolytes of Examples 1 to 3 and Comparative Example 1 of the present invention to a drying chamber are shown.

[0042] Figure 11 Impedance graphs are shown before and after the solid electrolytes of Examples 1 to 3 and Comparative Example 1 of the present invention were exposed to a drying chamber.

[0043] Figure 12 This is a graph showing the amount of hydrogen sulfide (H2S) generated when the solid electrolytes of Examples 1, 3 and Comparative Example 1 of the present invention were exposed to an atmosphere with a humidity of 65%.

[0044] Figure 13 This is a specific capacity diagram of each cycle of the pressed powder-molded battery cell of the solid electrolyte of Embodiment 1 and Comparative Example 1 of the present invention, which is exposed to a drying chamber. Detailed Implementation

[0045] To better understand this invention, a more detailed description will be provided below.

[0046] At this time, the terms or words used in this specification and claims should not be interpreted as having their usual or dictionary meanings; rather, they should be interpreted as meanings and concepts consistent with the technical concept of the present invention, based on the principle that the inventor can properly define the terms and concepts in order to best illustrate his or her invention.

[0047] <Solid Electrolytes> This invention provides a solid electrolyte.

[0048] Solid electrolytes are generally classified into oxide-based and sulfide-based solid electrolytes. Compared to oxide-based solid electrolytes, sulfide-based solid electrolytes have the advantages of higher lithium-ion conductivity and stability over a wide voltage range. However, they also have... Figure 1 The conventional sulfide-based solid electrolyte with the structure shown has the following problems: it reacts with atmospheric moisture to produce toxic hydrogen sulfide (H2S) gas, and has poor oxidation stability at high voltages, making it prone to side reactions with the cathode material when driven by high voltage.

[0049] Therefore, the inventors of this application discovered the following situation, thereby completing the present invention: Figure 2 As shown, when the lithium sites in argyrodite-type solid electrolytes are replaced by transition metals with higher oxidation numbers than lithium, ionic radii of 0.4 Å or more and 1.0 Å or less, and sulfur dissociation energies of 0.5 eV or more, the structural stability of the solid electrolyte is improved, as are its stability in air and under high voltage, and its ionic conductivity is excellent.

[0050] A solid electrolyte based on an embodiment of the present invention comprises at least a compound represented by the following chemical formula 1.

[0051] [Chemical Formula 1] Li a-nb M b PS c X d In the above chemical formula 1, M is selected from one or more transition metal elements with an ionic radius of 0.4 Å or greater and 1.0 Å or less, and a sulfur dissociation energy of 0.5 eV or greater. n represents the oxidation number of M above, and is greater than 1. X is one or more elements selected from Group 17 of the periodic table. 6≤a≤8, 0<b<0.2, 3≤c≤6, 0<d≤3, 5.2≤a-nb≤6.

[0052] According to one embodiment of the present invention, the above-mentioned 'a' represents the range of lithium (Li) molar ratios that a sulfide-based solid electrolyte with a sulfide-germanium sulfide crystal structure can have, which can be 6 or more and 8 or less. Specifically, it can be 6.1 or more, 6.2 or more, 6.3 or more, 6.4 or more, or 6.5 or more, and can be 7.8 or less, 7.6 or less, 7.4 or less, 7.2 or less, or 7 or less. In the present invention, the sulfide-germanium sulfide crystal structure refers to having the same structure as Ag5GeS6 ore.

[0053] According to one embodiment of the present invention, 'b' above represents the molar ratio of the transition metal (M) in the solid electrolyte based on an embodiment of the present invention, which can be greater than 0 and less than 0.2. Specifically, it can be 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, or 0.05 or more, and can be 0.18 or less, 0.16 or less, 0.14 or less, 0.12 or less, 0.1 or less, 0.08 or less, or 0.06 or less. When the above ranges are satisfied, the reactivity of the solid electrolyte with moisture in the air can be reduced, and the stability and ionic conductivity under high voltage can be improved.

[0054] According to one embodiment of the present invention, M is a transition metal having an oxidation number greater than that of lithium, an ionic radius of 0.4 Å or more and 1.0 Å or less, and a sulfur dissociation energy of 0.5 eV or more. It replaces the lithium sites of the solid electrolyte without participating in the electrochemical reaction and can form strong chemical bonds with sulfur atoms (S) within the crystal structure.

[0055] According to one embodiment of the present invention, the ionic radius of M is specifically 0.5 Å or more, 0.55 Å or more, 0.6 Å or more, 0.65 Å or more, or 0.7 Å or more, and may be 0.95 Å or less, 0.9 Å or less, 0.85 Å or less, or 0.8 Å or less. When the above range is satisfied, it has a similar ionic radius to Li. + With an ionic radius similar to that of 0.76 Å, substitution can proceed smoothly at lithium sites.

[0056] According to one embodiment of the present invention, the sulfur dissociation energy of M can specifically be 0.55 eV or more, 0.6 eV or more, 0.65 eV or more, 0.7 eV or more, 0.75 eV or more, 0.8 eV or more, or 0.85 eV or more. When the above range is satisfied, it can be considered that while forming strong chemical bonds with sulfur atoms (S) within the crystal structure, it does not reduce other physical properties of the solid electrolyte. In the present invention, the sulfur dissociation energy represents the minimum energy required for sulfur atoms to dissociate from the crystal structure.

[0057] Specifically, the sulfur dissociation energy (E) of M mentioned above s-dissociation The following method can be used to calculate the density functional theory (DFT) based on Li. 6-n×0.25 M 0.25 The energy (E) of the doped Argyrodite system composed of PS5Cl perfect ) and the energy (E) of crystal structure systems with S vacancies. s_vacancy ), calculate the S chemical potential (μ) from the alpha-S structure as the stable structure of S. s Then, it is calculated using the following mathematical formula 1.

[0058] In this case, the density functional theory (DFT) calculations mentioned above are performed using VASP (Vienna ab initiosimulation package), which calculates the structure and energy of atoms and electrons using the PAW (projector-augmented wave) method. The electron exchange-correlation function is calculated using the PBE (Perdew, Burke, Ernzerhof) model method based on GGA (generalized gradient approximation), with the kinetic energy cutoff set at 550 eV, and the calculation is performed using the 4×4×4 Monkhorst-Pack method.

[0059] [Mathematical Expression 1] E s-dissociation =E s_vacancy –E perfect +μ s In the above mathematical formula 1, E s-dissociation Indicates the sulfur dissociation energy. E s_vacancy This represents the energy of a crystal structure system with an S-vacancy. E perfect This indicates the energy of the doped Argyrodite crystal structure system. μ s This represents the chemical potential of S.

[0060] According to one embodiment of the present invention, as a specific example, M can be one or more selected from Co, Ni, Nb and Mg, and as a more specific example, it can be Co or Ni.

[0061] According to one embodiment of the present invention, n represents the oxidation number of M, which can be greater than the oxidation number (+1) of lithium (Li). Specifically, it can be 1.2 or more, 1.4 or more, 1.6 or more, 1.8 or more, or 2 or more, and can be 5 or less, 4 or less, 3 or less, or 2.5 or less. When the above ranges are satisfied, the crystal structure of the solid electrolyte can be maintained while reducing the generation of impurities during the manufacturing process.

[0062] According to one embodiment of the present invention, the above-mentioned c represents the molar ratio of sulfur atoms (S) in the solid electrolyte based on an embodiment of the present invention, which can be 3 or more and 6 or less. As a specific example, it can be 3.2 or more, 3.4 or more, 3.6 or more, 3.8 or more or 4 or more, and can be 5.8 or less, 5.6 or less, 5.4 or less, 5.2 or less or 5 or less.

[0063] According to an embodiment of the present invention, the above-mentioned d represents the molar ratio of halogen element (X) in the solid electrolyte based on an embodiment of the present invention, which can be greater than 0 and less than 3. As a specific example, it can be more than 0.2, more than 0.4, more than 0.6, more than 0.8 or more than 1, and can be less than 3.8, less than 3.6, less than 3.4, less than 3.2 or less.

[0064] According to an embodiment of the present invention, X is one or more elements selected from Group 17 of the periodic table. As a specific example, it can be one or more elements selected from F, Cl, Br, and I.

[0065] According to one embodiment of the present invention, when X is a variety of halogen elements, d can represent the total molar ratio of X. For example, when X is Cl and Br, d represents the sum of the molar ratios of Cl and Br. According to one embodiment of the present invention, a-nb represents the molar ratio of Li in the solid electrolyte based on an embodiment of the present invention, which can be 5.2 or more and 6 or less. As specific examples, it can be 5.22 or more, 5.24 or more, 5.26 or more, 5.28 or more, or 5.3 or more, and can be 5.9 or less, 5.8 or less, 5.7 or less, 5.6 or less, or 5.5 or less. When the above ranges are satisfied, the sulfide-germanium ore-type crystal structure can be maintained, the reactivity of the solid electrolyte with moisture in the air can be reduced, and the stability and ionic conductivity under high voltage can be improved.

[0066] A solid electrolyte based on an embodiment of the present invention may specifically comprise a compound represented by the following chemical formula 2.

[0067] [Chemical Formula 2] Li a-nb □ nb-b M b PS c X d In the above chemical formula 2, M is selected from one or more of Co, Ni, Nb, and Mg. □ represents a lithium site vacancy. n represents the oxidation number of M above, and is greater than 1. X is one or more elements selected from Group 17 of the periodic table. 6≤a≤8, 0<b<0.2, 3≤c≤6, 0<d≤3, 5.2≤a-nb≤6, 0<nb-b≤2.8.

[0068] In the above chemical formula 2, the descriptions of a, b, c, d, n and a-nb are the same as those in the above chemical formula 1, so the repeated descriptions are omitted.

[0069] According to one embodiment of the present invention, the aforementioned □ represents a lithium site vacancy. As the lithium site (Li-site) is replaced by a transition metal having a higher oxidation number than lithium (Li), this vacancy can be formed in the ionic crystal structure of the solid electrolyte through Schottky or Frenkel defects, which are site defects, and lithium ions (Li) can be formed. + The diffusion path of .

[0070] According to one embodiment of the present invention, the above-mentioned nb-b can be the molar ratio of lithium site vacancies in the solid electrolyte based on an embodiment of the present invention, which can be greater than 0 and less than 2.8. As a specific example, it can be greater than 0.1, greater than 0.2, greater than 0.3, greater than 0.4, or greater than 0.5, and can be less than 2.6, less than 2.4, less than 2.2, or less than 2. When the above range is satisfied, the sterhenite-type crystal structure can be maintained, the reactivity of the solid electrolyte with moisture in the air can be reduced, and the stability and ionic conductivity under high voltage can be improved.

[0071] The solid electrolyte based on an embodiment of the present invention may more specifically comprise a compound represented by the following chemical formula 3.

[0072] [Chemical Formula 3] Li 5.5-nb □ nb-b M b PS 4.5 Cl c1 Br c2 In the above chemical formula 3, M is selected from one or more of Co, Ni, Nb, and Mg. □ represents a lithium site vacancy. n is the oxidation number of M mentioned above. 0.05≤b<0.2, 5.2≤5.5-nb≤6, 0<c1≤1, 0<c2≤1, 0<nb-b≤2.8.

[0073] A solid electrolyte based on an embodiment of the present invention comprises a compound having the above-described composition, thereby having an agyrodite-type crystal structure or a crystal structure belonging to space group F-43m.

[0074] According to an embodiment of the present invention, the solid electrolyte has an a-axis lattice constant calculated by Rietveld analysis of 9.9 Å or less. Specific examples include 9.895 Å or less, 9.89 Å or less, 9.885 Å or less, 9.88 Å or less, 9.875 Å or less, 9.87 Å or less, or 9.865 Å or less, and can be 9.0 Å or more, 9.1 Å or more, 9.2 Å or more, 9.3 Å or more, 9.4 Å or more, or 9.5 Å or more. The above range can be satisfied by replacing the lithium sites in the solid electrolyte with a transition metal having an oxidation number greater than that of lithium and forming strong chemical bonds with sulfur and halogen elements within the crystal structure.

[0075] When the solid electrolyte according to an embodiment of the present invention is measured with a Hunter Lab colorimeter, the L value is 8 or higher and 46 or lower. Specifically, it can be 9 or higher, 10 or higher, 11 or higher, 12 or higher, 13 or higher, or 14 or higher, and can be 44 or lower, 42 or lower, 40 or lower, 38 or lower, 36 or lower, or 34 or lower. The above range can be satisfied by replacing the lithium sites in the solid electrolyte with a transition metal having an oxidation number greater than that of lithium and forming strong chemical bonds with sulfur and halogen elements within the crystal structure.

[0076] According to an embodiment of the present invention, the solid electrolyte exhibits no peaks at 2θ positions of 27±0.5°, 36±0.5°, and 40±1° in the XRD pattern measured using CuKα rays, and no peaks at 2θ positions of 35±0.5° and 46±0.5°. This is because the lithium sites within the solid electrolyte are replaced by transition metals with oxidation numbers greater than lithium and which form strong chemical bonds with sulfur and halogen elements within the crystal structure.

[0077] The solid electrolyte based on an embodiment of the present invention, having the above-described structure and composition, is able to satisfy the requirements of excellent ionic conductivity, excellent high voltage driving stability, low resistance, and low moisture reactivity.

[0078] The ionic conductivity of the solid electrolyte according to an embodiment of the present invention can be 7 mS / cm or higher. As a specific example, it can be 7.5 mS / cm or higher, 8 mS / cm or higher, 8.5 mS / cm or higher, 9 mS / cm or higher, or 9.5 mS / cm or higher.

[0079] According to an embodiment of the present invention, the resistance value of the solid electrolyte calculated based on the impedance measured by EIS can be less than 7Ω. As a specific example, it can be less than 6.5Ω, less than 6Ω, less than 5.5Ω, or less than 5Ω.

[0080] According to an embodiment of the present invention, the ratio (P1:P2) of the peak intensity (P1) observed at a position of 2θ = 25.5 ± 0.5° in the XRD pattern measured using CuKα rays to the peak intensity (P2) observed at a position of 2θ = 25.5 ± 0.5° in the XRD pattern measured using CuKα rays after the solid electrolyte has been exposed to a drying chamber at a dew point temperature of -60°C for 24 hours can be 1:0.7 or higher and 1:0.95 or lower. As specific examples, it can be 1:0.71 or higher, 1:0.72 or higher, 1:0.73 or higher, 1:0.74 or higher, or 1:0.75 or higher, and it can be 1:0.9 or lower, 1:0.88 or lower, 1:0.86 or lower, 1:0.84 or lower, 1:0.82 or lower, or 1:0.8 or lower.

[0081] According to an embodiment of the present invention, the ratio (I1:I2) of the ionic conductivity (I1) measured for the solid electrolyte to the ionic conductivity (I2) measured after the solid electrolyte has been exposed to a drying chamber at a dew point temperature of -60°C for 24 hours can be 1:0.5 or more and 1:0.8 or less. As specific examples, it can be 1:0.52 or more, 1:0.54 or more, 1:0.56 or more, 1:0.58 or more, or 1:0.6 or more, and it can be 1:0.78 or less, 1:0.76 or less, 1:0.74 or less, 1:0.72 or less, or 1:0.7 or less.

[0082] Based on an embodiment of the present invention, 0.1g of the solid electrolyte is placed in an acrylic box measuring 130mm × 130mm × 250mm. After exposure to air at 65% humidity for 20 minutes using a Gas Tiger 6000 device, the amount of hydrogen sulfide (H2S) generated can be less than 310ppm. As a specific example, it can be less than 305ppm, less than 300ppm, less than 295ppm, less than 290ppm, less than 285ppm, less than 280ppm, less than 275ppm, or less than 270ppm.

[0083] <Solid Electrolyte Manufacturing Methods> The present invention provides a method for manufacturing the above-described solid electrolyte.

[0084] A method for manufacturing a solid electrolyte according to an embodiment of the present invention includes at least the following steps: (S1) preparing lithium raw material, phosphorus sulfide raw material, transition metal raw material and halogen element raw material, and pulverizing and mixing them; and (S2) calcining the product of the above step (S1) at a temperature range of 400°C or higher and 500°C or lower, wherein the transition metal raw material is any one or more metal compounds selected from transition metal elements with an ionic radius of 0.4 Å or higher and 1.0 Å or lower and a sulfur dissociation energy of 0.5 eV or higher.

[0085] The following describes in more detail a method for manufacturing a solid electrolyte based on an embodiment of the present invention, following each step.

[0086] Step (S1) A solid electrolyte manufacturing method according to an embodiment of the present invention may include the steps of preparing lithium raw materials, phosphorus sulfide raw materials, transition metal raw materials and halogen element raw materials, and crushing and mixing them (S1).

[0087] According to one embodiment of the present invention, the lithium raw material can be lithium sulfide (Li2S), but is not limited thereto.

[0088] According to one embodiment of the present invention, the above-mentioned phosphorus sulfide raw material can be phosphorus pentasulfide (P2S5), but is not limited thereto.

[0089] According to one embodiment of the present invention, the aforementioned transition metal raw material can be any one or more metal compounds selected from Co, Ni, Nb, and Mg. As a specific example, the aforementioned transition metal raw material can be any one or more divalent metal compounds selected from Co, Ni, Nb, and Mg. As a more specific example, it can be any one or more divalent metal halides selected from Co, Ni, Nb, and Mg. According to one embodiment of the present invention, the aforementioned transition metal raw material can be a metal compound of Co or Ni. As a specific example, it can be a divalent metal compound of Co or Ni. As a more specific example, it can be a divalent metal halide of Co or Ni.

[0090] According to one embodiment of the present invention, the above-mentioned halogen element raw material can be a metal halide, and as a specific example, it can be a lithium halide.

[0091] According to an embodiment of the present invention, in the above step (S1), the appropriate amount of each raw material substance can be weighed and then crushed and mixed according to the composition of the above chemical formulas 1 to 3.

[0092] According to one embodiment of the present invention, the pulverization in step (S1) above can be performed by a high-energy ball mill. As a specific example, it can be performed for more than 8 hours and less than 15 hours under conditions of more than 300 rpm and less than 700 rpm.

[0093] Step (S2) A solid electrolyte manufacturing method according to an embodiment of the present invention may include a step (S2) of calcining the product of the above step (S1) in a temperature range of 400°C or higher and 500°C or lower.

[0094] According to an embodiment of the present invention, the above step (S2) can be performed in a temperature range of 300°C or higher and 600°C or lower. As a specific example, it can be performed in a temperature range of 320°C or higher, 340°C or higher, 360°C or higher, 380°C or higher, or 400°C or higher, and in a temperature range of 580°C or lower, 560°C or lower, 540°C or lower, 520°C or lower, or 500°C or lower.

[0095] According to one embodiment of the present invention, the above step (S2) can be performed for more than 4 hours and less than 8 hours. As a specific example, it can be performed for more than 4.5 hours, more than 5 hours or more than 5.5 hours, and can be performed for less than 7.5 hours, less than 7 hours or less than 6.5 hours.

[0096] According to one embodiment of the present invention, the above step (S2) can be performed in a calcining furnace filled with inert gas, and as a specific example of the inert gas, it can be argon.

[0097] The solid electrolyte manufacturing method according to an embodiment of the present invention may further include a step (S3) of pulverizing the product of the above step (S2) and controlling the particle size, wherein the above step (S3) can be performed by high energy ball milling.

[0098] <All-solid-state batteries> The present invention provides an all-solid-state battery comprising the above-described solid electrolyte.

[0099] According to one embodiment of the present invention, the above-mentioned all-solid-state battery may be a structure formed by sequentially stacking a negative electrode current collector, an intermediate layer, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector.

[0100] According to one embodiment of the present invention, the negative current collector may be a plate-shaped substrate with conductivity. Specifically, the negative current collector may be in the form of a sheet, a thin film, or a foil.

[0101] According to one embodiment of the present invention, the aforementioned negative electrode current collector may include a material that does not react with lithium. Specifically, the aforementioned negative electrode current collector may include at least one selected from Ni, Cu, SUS (Stainless Steel), and combinations thereof.

[0102] According to one embodiment of the present invention, the intermediate layer may include a negative electrode active material, a solid electrolyte, a binder, etc.

[0103] According to one embodiment of the present invention, the above-mentioned negative electrode active material is not particularly limited, and can be, for example, a carbon active material or a metal active material.

[0104] According to one embodiment of the present invention, the carbon active material can be graphite such as mesophase carbon microspheres (MCMB) or highly oriented pyrolytic graphite (HOPG), or amorphous carbon materials such as hard carbon or soft carbon.

[0105] According to one embodiment of the present invention, the above-mentioned metal active material may be In, Al, Si, Sn, and alloys containing at least one of these elements.

[0106] According to one embodiment of the present invention, the above-mentioned solid electrolyte can be a sulfide-based solid electrolyte. As a specific example, it can be selected from Li 7-x PS 6-x A x (0≤x≤1, A is selected from Br, Cl and I or more), Li 10 GeP2S 12 Li3PS4, Li7P3S 11 , Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li 2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (Where m and n are positive numbers, and Z is one of Ge, Zn, and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In) and one or more combinations thereof, or one or more compounds selected from those represented by the above chemical formulas 1 to 3.

[0107] According to one embodiment of the present invention, the conductive agent can be a structure that forms an electron conduction path within the electrode. The conductive agent can be an sp2 carbon material such as carbon black, conducting graphite, acetylene black, or carbon nanotube, or graphene.

[0108] According to one embodiment of the present invention, the adhesive can be BR (Butadiene rubber), NBR (Nitrile butadiene rubber), HNBR (Hydrogenated nitrile butadiene rubber), PVDF (polyvinylidene difluoride), PTFE (polytetrafluoroethylene), CMC (carboxymethyl cellulose), etc.

[0109] According to one embodiment of the present invention, the intermediate layer may include a lithium alloy metal capable of forming an alloy with lithium.

[0110] According to one embodiment of the present invention, the lithium alloy metal can be one or more selected from tin (Sn), cadmium (Cd), silver (Ag), gold (Au), platinum (Pt), palladium (Pd), magnesium (Mg), zinc (Zn) and combinations thereof. As a specific example, it can be one or more selected from magnesium (Mg), zinc (Zn), silver (Ag), gold (Au) and combinations thereof. As a more specific example, it can be magnesium (Mg).

[0111] According to one embodiment of the present invention, when the intermediate layer comprises a lithium alloy metal, the lithium alloy metal can be manufactured by methods such as sputtering or chemical vapor deposition.

[0112] According to one embodiment of the present invention, the solid electrolyte layer described above serves to transfer lithium ions between the positive electrode and the negative electrode.

[0113] The solid electrolyte contained in the solid electrolyte layer according to an embodiment of the present invention may be one or more compounds selected from those represented by the above chemical formulas 1 to 3.

[0114] According to one embodiment of the present invention, the above-mentioned positive electrode active material layer may include a positive electrode active material, a solid electrolyte, a conductive agent, a binder, etc.

[0115] According to one embodiment of the present invention, the above-mentioned positive electrode active material is not particularly limited, and can be, for example, an oxide active material or a sulfide active material.

[0116] According to one embodiment of the present invention, the above-mentioned oxide active material may be LiCoO2, LiMnO2, LiNiO2, LiVO2, or Li 1+x Ni 1 / 3 Co 1 / 3 Mn 1 / 3O2 and other rock salt layer-type active substances, LiMn2O4, Li(Ni) 0.5 Mn 1.5 Spinel-type active materials such as LiNiVO4 and LiCoVO4, olivine-type active materials such as LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4, silicon-containing active materials such as Li2FeSiO4 and Li2MnSiO4, and LiNi 0.8 Co (0.2-x) Al x O2 (0 < x < 0.2) and other transition metals are replaced by different metals in rock salt layer-type active materials, Li 1+x Mn 2-x-y M y O4 (where M is at least one of Al, Mg, Co, Fe, Ni, and Zn, 0 < x + y < 2) and other transition metals replaced by different metals, spinel-type active materials, Li4Ti5O 12 Lithium titanate, etc.

[0117] According to one embodiment of the present invention, the above-mentioned sulfide active material may be copper Chevrel, iron sulfide, cobalt sulfide, nickel sulfide, etc.

[0118] According to one embodiment of the present invention, the above-mentioned solid electrolyte can be a sulfide-based solid electrolyte. As a specific example, it can be selected from Li 7-x PS 6-x A x (0≤x≤1, A is selected from Br, Cl and I or more), Li 10 GeP2S 12 Li3PS4, Li7P3S 11 , Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li 2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (Where m and n are positive numbers, and Z is one of Ge, Zn, and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y(where x and y are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In) and one or more combinations thereof, or one or more compounds selected from those represented by the above chemical formulas 1 to 3, more preferably one or more compounds selected from those represented by the above chemical formulas 1 to 3.

[0119] According to one embodiment of the present invention, the conductive agent and adhesive described above are as described above, and therefore detailed descriptions thereof are omitted.

[0120] According to one embodiment of the present invention, the positive current collector may be a plate-shaped substrate with conductivity. Specifically, the positive current collector may have a sheet-like or foil-like shape.

[0121] According to one embodiment of the present invention, the positive current collector may contain at least one selected from indium, copper, magnesium, aluminum, stainless steel, iron, and combinations thereof.

[0122] The embodiments of the present invention will now be described in detail to enable those skilled in the art to readily implement it. However, the present invention can be implemented in many different ways and is not limited to the embodiments described herein.

[0123] Example 1-Li 5.4 Co 0.05 PS 4.5 Cl 0.75 Br 0.75 Prepare 2g of lithium sulfide (Li₂S) as a lithium raw material, phosphorus pentasulfide (P₂S₅) as a phosphorus sulfide raw material, cobalt(II) chloride (CoCl₂) and cobalt(II) bromide (CoBr₂) as transition metal raw materials, and lithium chloride (LiCl) and lithium bromide (LiBr) as halogen raw materials. Mix the raw materials according to the Li 5.4 Co 0.05 PS 4.5 Cl 0.75 Br 0.75 The components were weighed and placed into a Si3N4 jar, and subjected to high-energy ball milling at a rotation speed of 500 rpm for 12 hours.

[0124] The high-energy ball-milled product was placed in a sealed quartz tube filled with argon gas and heated to 450°C at a rate of 2.5°C / min. The product was then calcined at 450°C for 6 hours to obtain a solid electrolyte.

[0125] Example 2-Li 5.3 Co 0.1 PS 4.5 Cl 0.75 Br 0.75 According to Li 5.3 Co 0.1 PS 4.5 Cl 0.75 Br 0.75 Weigh the raw materials from Example 1, and otherwise use the same method as in Example 1 to prepare a solid electrolyte.

[0126] Example 3-Li 5.4 Ni 0.05 PS 4.5 Cl 0.75 Br 0.75 Lithium sulfide (Li₂S) is prepared as a lithium raw material; phosphorus pentasulfide (P₂S₅) is prepared as a phosphorus sulfide raw material; nickel(II) chloride (NiCl₂) and nickel(II) bromide (NiBr₂) are prepared as transition metal raw materials; and lithium chloride (LiCl) and lithium bromide (LiBr) are prepared as halogen raw materials, totaling 2g. According to Li 5.4 Ni 0.05 PS 4.5 Cl 0.75 Br 0.75 The composition of the solid electrolyte was prepared by weighing each raw material and, otherwise, by using the same method as in Example 1.

[0127] Comparative Example 1-Li 5.5 PS5Cl 0.75 Br 0.75 Prepare 2g of lithium sulfide (Li₂S) as a lithium raw material, phosphorus pentasulfide (P₂S₅) as a phosphorus sulfide raw material, and lithium chloride (LiCl) and lithium bromide (LiBr) as halogen raw materials. According to Li 5.5 PS5Cl 0.75 Br 0.75 The composition of the solid electrolyte was prepared by weighing each raw material and, otherwise, by using the same method as in Example 1.

[0128] Comparative Example 2-Li 5.1 Co 0.2 PS 4.5 Cl 0.75 Br 0.75 According to Li 5.1 Co 0.2 PS 4.5 Cl 0.75 Br 0.75 Weigh the raw materials from Example 1, and otherwise use the same method as in Example 1 to prepare a solid electrolyte.

[0129] Comparative Example 3-Li 4.9 Co 0.3 PS 4.5 Cl 0.75 Br 0.75 According to Li 4.9 Co 0.3 PS 4.5 Cl 0.75 Br 0.75 Weigh the raw materials from Example 1, and otherwise use the same method as in Example 1 to prepare a solid electrolyte.

[0130] Comparative Example 4-Li 5.35 Al 0.05 PS 4.5 Cl 0.75 Br 0.75 Prepare 2g of lithium sulfide (Li₂S) as a lithium raw material, phosphorus pentasulfide (P₂S₅) as a phosphorus sulfide raw material, aluminum(III) chloride (AlCl₃) and aluminum(III) bromide (AlBr₃) as non-transition metal raw materials, and lithium chloride (LiCl) and lithium bromide (LiBr) as halogen raw materials. According to Li 5.35 Al 0.05 PS 4.5Cl 0.75 Br 0.75 Weigh each raw material and place it in a Si3N4 container. Perform high-energy ball milling at a rotation speed of 500 rpm for 12 hours.

[0131] The high-energy ball-milled product was placed in a sealed quartz tube filled with argon gas and heated to 450°C at a rate of 2.5°C / min. It was then calcined at 450°C for 6 hours to obtain a solid electrolyte.

[0132] Experimental Example 1: Structural Analysis and Characteristic Evaluation of Solid Electrolytes 1) SEM-EDS analysis SEM images and EDS mappings of the solid electrolytes prepared in Example 1 and Comparative Example 1 are shown below. Figure 3 and Figure 4 The SEM apparatus used was the Apreo 2S from Thermo Fisher Scientific, and the SEM-EDS apparatus used was the Chemi SEM apparatus from Thermo Fisher Scientific.

[0133] Reference Figure 3 and Figure 4 It can be confirmed that all elements are uniformly distributed in the solid electrolytes of Example 1 and Comparative Example 1.

[0134] 2) XRD analysis XRD patterns were obtained using Miniflex (Rigaku Corporation) for both the solid electrolytes of Examples 1 to 3 and Comparative Examples 1 to 3, under conditions of 40 kV voltage, 15 mA current, CuKα, 2θ (Bragg angle) = 10° to 80°, and scan rate = 2° / 60 sec. These patterns are shown below. Figure 5 and Figure 6 .

[0135] Reference Figure 5 and Figure 6 It can be confirmed that even if the lithium sites in Examples 1 to 3 are replaced by preferred transition metal elements, the argyrodite structure, as in Comparative Example 1, can still be well maintained.

[0136] Furthermore, in Examples 1 and 2 where cobalt was substituted at a preferred content, the argyrodite structure was well maintained. However, in Comparative Examples 2 and 3 where cobalt was substituted at a higher content than preferred, peaks caused by impurities (CoS) were observed. In particular, in Comparative Example 2, the peak intensity representing the argyrodite structure was confirmed to be weakened. This is because in Comparative Examples 2 and 3, when the amount of cobalt substitution was greater than necessary, the lithium content decreased, resulting in a large number of vacancies, making it difficult to maintain the argyrodite structure.

[0137] 3) Lattice constant and space group analysis The space groups of the solid electrolytes of Examples 1 to 3 and Comparative Example 1, obtained by calculating the XRD data of the Examples and Comparative Examples obtained by the above measurements using the Rietveld refinement method, are shown in Table 1 below.

[0138] Referring to Table 1 below, it can be confirmed that even if the lithium sites are replaced by preferred transition metals, the F-43m crystal structure can still be maintained.

[0139] [Table 1] Furthermore, by comparing the a-axis lattice constant of Example 1 (9.86 Å) and the a-axis lattice constant of Comparative Example 1 (9.93 Å) obtained by calculating the XRD data of the Examples and Comparative Examples obtained by the above measurements using the Rietveld refinement method, it can be confirmed that the lattice constant of the solid electrolyte of Example 1 in which the lithium site is replaced by a preferred transition element (M) is smaller than that of Comparative Example 1. This is because the strong chemical bonds between MS, M-Cl, and M-Br lead to structural contraction.

[0140] 4) Apparent color measurement The L, a, and b values ​​of the solid electrolytes based on Examples 1 and 2 and Comparative Examples 1 and 3 were measured using a Hunter Lab colorimeter and are shown in Table 2 below. Additionally, images taken of the solid electrolytes based on Examples 1 and 2 and Comparative Examples 1 and 3 are shown below. Figure 7 .

[0141] [Table 2] Refer to Table 2 above and Figure 7 It can be confirmed that as the amount of cobalt substitution increases, the color of the solid electrolyte gradually darkens, while the L value of the colorimeter decreases.

[0142] 5) EIS measurement The impedance of each solid electrolyte prepared in Examples 1 to 3 and Comparative Examples 2 to 4 was measured using electrochemical impedance spectroscopy (EIS) at a frequency of 1 MHz to 10 mHz and an amplitude of 10 mV, and is shown in the figure. Figure 8 .

[0143] Then, the resistance values ​​of each solid electrolyte prepared in Examples 1 to 3 and Comparative Examples 2 to 4 were calculated based on the measured impedance, and the ionic conductivity was calculated using the following mathematical formula 2, as shown in Table 3 below.

[0144] [Mathematical Expression 2] In the above mathematical formula 2, R b For resistance, t is the thickness of the solid electrolyte sample. A is the cross-sectional area of ​​the solid electrolyte sample (1.3273 cm²). 2 ).

[0145] [Table 3] Refer to Table 3 above and Figure 8 It can be confirmed that the embodiments in which the lithium sites are replaced by the preferred transition metal (M) in a preferred amount have excellent ionic conductivity and low resistance.

[0146] On the other hand, in Comparative Examples 2 and 3, where the amount of cobalt substitution at the lithium sites exceeded the preferred content, it was confirmed that the ionic conductivity was low and the resistance value was high. The reason for this was that as the cobalt content increased, the content of diffusible lithium decreased.

[0147] For Comparative Example 4, where the lithium sites are replaced by Al (the sulfur dissociation energy calculated using the above mathematical formula 1 is 0.46 eV), it can be confirmed that the resistance value is significantly higher.

[0148] Experimental Example 2: Battery Characteristic Evaluation 1) Manufacturing of pressed powder molded battery cells Powder-molded cells in which the solid electrolytes of Example 1 and Comparative Example 1 are applied to the electrolyte layer are manufactured in the following manner.

[0149] First, the positive electrode active material (LiNi coated with LiNbO3) is... 0.8 Co 0.1 Mn 0.1 O2), solid electrolyte (Li6PS5Cl) 0.5 Br0.5 The following ingredients were added to a Pulverisette 23 Mini Mill at a weight ratio of 70:29:1:1:1: 100 wt% (by weight) to prepare a slurry: 20 mg / cm³ of nitrile rubber, binder (containing 2.5 wt% nitrile rubber dissolved in a butyl butyrate solution), and SuperC65. The slurry was mixed at 20 rpm for 1 hour to prepare a slurry. 2 The loading capacity is coated onto a 10μm thick positive electrode current collector made of aluminum and dried in a vacuum oven at 100°C for 12 hours to manufacture a 12Ф positive electrode.

[0150] An electrolyte layer is formed by pressurizing 150 mg of the solid electrolytes of Example 1 and Comparative Example 1 at a pressure of 45 MPa on the obtained positive electrode. A lithium foil with a thickness of 0.2 mm is formed on the formed electrolyte layer by pressurizing at a pressure of 45 MPa, thereby manufacturing a pressed powder molded battery cell.

[0151] 2) Ratio Characteristics Evaluation Each pressed-powder cell manufactured using the solid electrolytes of Example 1 and Comparative Example 1 was pre-cycled at 25°C in CC-CV (constant current-constant voltage) mode at 0.1C (1C=185mAh / g) to 4.25V, and then discharged at 25°C in CC mode at 0.1C (1C=185mAh / g) to 2.5V; the first cycle was performed at 25°C in CC-CV mode at 0.1C (1C=185mAh / g) to 4.25V, and then discharged at 25°C in CC mode at 0.1C (1C=185mAh / g) to 2.5V; the second cycle was performed at 25°C in CC-CV mode at 0.2C (1C=185mAh / g) to 4.25V, and then discharged at 25°C in CC mode at 0.2C (1C=185mAh / g) to 2.5V; the third cycle was performed at 25°C in CC-CV mode at 0.1C (1C=185mAh / g) to 4.25V. The first cycle involves charging to 4.25V at 0.33C (1C=185mAh / g) in CC-CV mode at 25℃, and discharging to 2.5V at 0.33C (1C=185mAh / g). The second cycle involves charging to 4.25V at 0.5C (1C=185mAh / g) in CC-CV mode at 25℃, and discharging to 2.5V at 0.5C (1C=185mAh / g) in CC mode at 25℃. The third cycle involves charging to 4.25V at 1C (1C=185mAh / g) in CC-CV mode at 25℃, and discharging to 2.5V at 1C (1C=185mAh / g) in CC mode at 25℃. The fourth cycle involves charging to 4.25V at 2C (1C=185mAh / g) in CC-CV mode at 25℃, and discharging to 2.5V at 2C (1C=185mAh / g) in CC mode at 25℃. The measured charging capacity (mAh / g), discharging capacity (mAh / g), and coulombic efficiency (%) are shown in Table 4 below.

[0152] [Table 4] Referring to Table 4 above, it can be confirmed that, compared with Comparative Example 1, Example 1, in which the lithium site is replaced by cobalt, exhibits superior initial discharge capacity and initial coulombic efficiency. Furthermore, it can be confirmed that the discharge capacity and coulombic efficiency at a high current density of 2C are even more superior. The reason for this is that the cobalt substitution of the lithium site increases the structural stability of the solid electrolyte, suppresses side reactions with the positive and negative electrodes, and reduces the interfacial resistance.

[0153] 3) Lifetime characteristics evaluation Each pressed-powder cell manufactured using the solid electrolytes of Example 1 and Comparative Example 1 was charged to 4.25V at 0.1C (1C=185mAh / g) in CC-CV mode at 25°C during pre-cycling, and discharged to 2.5V at 0.1C (1C=185mAh / g) in CC mode at 25°C. From the first to the twentieth cycle, the cells were charged to 4.25V at 0.5C (1C=185mAh / g) in CC-CV mode, and discharged to 2.5V at 0.5C (1C=185mAh / g) in CC mode at 25°C. The specific capacity and coulombic efficiency measured for each cycle are plotted in the figure. Figure 9 .

[0154] [Table 5] Refer to Table 5 above and Figure 9 It can be confirmed that, based on the 20th cycle, the discharge capacity of the pressed powder-formed battery cell of Example 1 is 157.0 mAh / g, with a capacity retention of 92.0%; while the discharge capacity of the pressed powder-formed battery cell of Comparative Example 1 is 154.8 mAh / g, with a capacity retention of 91.5%. This confirms that cobalt substitution at the lithium sites improves the lifetime characteristics. The reason for this is that cobalt substitution at the lithium sites increases the structural stability of the solid electrolyte.

[0155] Experimental Example 3 – Environmental Resistance Evaluation 1) XRD measurement One g of each solid electrolyte from Examples 1 to 3 and Comparative Example 1 was evenly spread on sulfuric acid paper, placed in a petri dish, and then treated in a drying chamber at a dew point temperature of -60°C. XRD patterns were obtained using a Miniflex (Rigaku) ​​XRD instrument at a voltage of 40 kV, a current of 15 mA, a CuKα electron beam at 2θ (Bragg angle) of 22°–34°, and a scan rate of 2° / 60 seconds, for three cases: ① no exposure to the drying chamber, ② exposure for 6 hours, and ③ exposure for 24 hours. The results are shown below. Figure 10 .

[0156] Reference Figure 10 It can be confirmed that when the lithium site is replaced by a preferred transition metal (M), there is no reduction or shift in peak intensity even after prolonged exposure to a drying chamber. This confirms that the solid electrolyte with the lithium site replaced by the preferred transition metal (M) has excellent environmental resistance.

[0157] 2) EIS measurement One g of each solid electrolyte from Examples 1 to 3 and Comparative Example 1 was evenly spread on sulfuric acid paper, placed in a petri dish, and then treated in a drying chamber at a dew point temperature of -60°C. For three conditions: ① no exposure to the drying chamber, ② exposure for 6 hours, and ③ exposure for 24 hours, the impedance and ionic conductivity (calculated as described in Experimental Example 2) were measured using electrochemical impedance spectroscopy (EIS) at a frequency of 1 MHz to 10 mHz and an amplitude of 10 mV. The results are shown below. Figure 11 .

[0158] Reference Figure 11 It can be confirmed that: the ionic conductivity retention rate (ionic conductivity after 24 hours of exposure / unexposed ionic conductivity × 100) of the solid electrolyte based on Example 1 is 70%; the ionic conductivity retention rate (ionic conductivity after 24 hours of exposure / unexposed ionic conductivity × 100) of the solid electrolyte based on Example 2 is 83.2%; the ionic conductivity retention rate (ionic conductivity after 24 hours of exposure / unexposed ionic conductivity × 100) of the solid electrolyte based on Example 3 is 65.1%; and the ionic conductivity retention rate (ionic conductivity after 24 hours of exposure / unexposed ionic conductivity × 100) of the solid electrolyte based on Comparative Example 1 is 47%. The reason for this is that the preferred transition metal (M) atoms substituted at the lithium sites form strong chemical bonds with the sulfur (S) atoms present in the crystal structure of the solid electrolyte, inhibiting the reaction between water (H2O) and oxygen (O2) with sulfur (S).

[0159] 3) H2S generation measurement 0.1 g of each of the solid electrolytes based on Examples 1 and 3 and Comparative Example 1 were placed in an acrylic box measuring 130 mm × 130 mm × 250 mm. The amount of hydrogen sulfide (H2S) generated after 20 minutes of exposure to air at 65% humidity was measured using a Gas Tiger 6000 instrument. The hourly hydrogen sulfide generation is then displayed. Figure 12 .

[0160] Reference Figure 12 It can be confirmed that: the amount of hydrogen sulfide generated after exposing the solid electrolyte of Example 1 to the atmosphere at 65% humidity for 20 minutes was 267.3 ppm; the amount of hydrogen sulfide generated after exposing the solid electrolyte of Example 3 to the atmosphere at 65% humidity for 20 minutes was 284.6 ppm; and the amount of hydrogen sulfide generated after exposing the solid electrolyte of Comparative Example 1 to the atmosphere at 65% humidity for 20 minutes was 360.9 ppm.

[0161] Therefore, it can be confirmed that the solid electrolyte of Example 1 has a hydrogen sulfide generation reduction of approximately 28% compared to the solid electrolyte of Comparative Example 1; and the solid electrolyte of Example 3 has a hydrogen sulfide generation reduction of 21% compared to the solid electrolyte of Comparative Example 1. The reason for this is that the preferred transition metal (M) atoms substituted at the lithium sites form strong chemical bonds with the sulfur (S) atoms present in the crystal structure of the solid electrolyte, thus suppressing the reaction between water (H2O) and oxygen (O2) with sulfur (S).

[0162] 4) Evaluation of the life characteristics of pressed powder molded battery cells After exposing each solid electrolyte from Example 1 and Comparative Example 1 to a drying chamber at a dew point temperature of -60°C for 6 hours, they were applied to the solid electrolyte layer to manufacture a pressed powder molded battery cell, as described in Experimental Example 2 above. Subsequently, each of the fabricated powder-molded cells was pre-cycled at 25°C in CC-CV mode at 0.1C (1C=185mAh / g) to 4.25V, and then discharged at 25°C in CC mode at 0.1C (1C=185mAh / g) to 2.5V. From the first to the fifteenth cycle, the cells were charged to 4.25V in CC-CV mode at 0.5C (1C=185mAh / g), and then discharged at 25°C in CC mode at 0.5C (1C=185mAh / g) to 2.5V. The specific capacity and coulombic efficiency measured for each cycle are plotted below. Figure 13 .

[0163] Reference Figure 13 It can be confirmed that, based on the fifteenth cycle, the discharge capacity of the pressed powder-formed battery cell of Example 1 is 163.1 mAh / g, with a capacity retention rate of 98.1%; the discharge capacity of the pressed powder-formed battery cell of Comparative Example 1 is 154.3 mAh / g, with a capacity retention rate of 97.9%. Therefore, it can be confirmed that, when exposed to the drying chamber, compared to the discharge capacity and capacity retention rate of Comparative Example 1 without cobalt substitution, Example 1, which has cobalt substitution at the lithium sites, exhibits superior discharge capacity and capacity retention rate. This is attributed to the fact that cobalt substitution at the lithium sites increases the structural stability of the solid electrolyte.

Claims

1. A solid electrolyte comprising a compound represented by the following chemical formula 1, [Chemical Formula 1] Li a-nb M b PS c X d In the chemical formula 1, M is selected from one or more transition metal elements with an ionic radius of 0.4 Å or greater and 1.0 Å or less, and a sulfur dissociation energy of 0.5 eV or greater. n represents the oxidation number of M, and is greater than 1. X is one or more elements selected from Group 17 of the periodic table. 6≤a≤8, 0<b<0.2, 3≤c≤6, 0<d≤3, 5.2≤a-nb≤6.

2. The solid electrolyte according to claim 1, comprising a compound represented by chemical formula 2. [Chemical Formula 2] Li a-nb □ nb-b M b PS c X d In the chemical formula 2, M is selected from one or more of Co, Ni, Nb, and Mg. □ represents a lithium site vacancy. n represents the oxidation number of M, and is greater than 1. X is one or more elements selected from Group 17 of the periodic table. 6≤a≤8, 0<b<0.2, 3≤c≤6, 0<d≤3, 5.2≤a-nb≤6, 0<nb-b≤2.

8.

3. The solid electrolyte according to claim 1, comprising a compound represented by the following chemical formula 3, [Chemical Formula 3] Li 5.5-nb □ nb-b M b PS 4.5 Cl c1 Br c2 In the chemical formula 3, M is selected from one or more of Co, Ni, Nb, and Mg. □ represents a lithium site vacancy. n represents the oxidation number of M, and is greater than 1. 0.05≤b<0.2, 5.2≤5.5-nb≤6, 0<c1≤1, 0<c2≤1, 0<nb-b≤2.

8.

4. The solid electrolyte according to claim 1, wherein, The solid electrolyte has a crystal structure belonging to space group F-43m.

5. The solid electrolyte according to claim 1, wherein, The solid electrolyte has a sulfosilgermanium ore-type crystal structure.

6. The solid electrolyte according to claim 1, wherein, The lattice constant of the a-axis calculated by Rietveld analysis is below 9.9 Å.

7. The solid electrolyte according to claim 1, wherein, When measuring the solid electrolyte using a Hunter Lab colorimeter The L value is 8 or higher and 46 or lower.

8. The solid electrolyte according to claim 1, wherein, There are no peaks at the positions of 2θ 27±0.5°, 36±0.5°, and 40±1° in the XRD pattern of the solid electrolyte measured using CuKα rays.

9. The solid electrolyte according to claim 1, wherein, There are no peaks at the positions of 2θ 35±0.5° and 46±0.5° in the XRD pattern of the solid electrolyte measured using CuKα rays.

10. The solid electrolyte according to claim 1, wherein, The resistance value calculated based on the impedance measured by EIS is less than 7Ω.

11. The solid electrolyte according to claim 1, wherein, The ionic conductivity of the solid electrolyte is above 7 mS / cm.

12. The solid electrolyte according to claim 1, wherein, The ratio of peak intensity P1 observed at a position of 2θ = 25.5 ± 0.5° in the XRD pattern of the solid electrolyte measured using CuKα rays to the peak intensity P2 observed at a position of 2θ = 25.5 ± 0.5° in the XRD pattern of the solid electrolyte measured using CuKα rays to the peak intensity P2 observed at a position of 2θ = 25.5 ± 0.5° in the XRD pattern of the solid electrolyte measured using CuKα rays to the peak intensity P2 after the solid electrolyte has been exposed to a drying chamber at a dew point temperature of -60°C for 24 hours is greater than or equal to 1:0.7 and less than or equal to 1:0.

95.

13. The solid electrolyte according to claim 1, wherein, The ratio I1:I2 of the ionic conductivity I1 measured for the solid electrolyte and the ionic conductivity I2 measured after the solid electrolyte has been exposed to a drying chamber at a dew point temperature of -60°C for 24 hours is greater than or equal to 1:0.5 and less than or equal to 1:0.

8.

14. The solid electrolyte according to claim 1, wherein, 0.1g of the solid electrolyte was placed in an acrylic box measuring 130mm×130mm×250mm. After exposure to air at 65% humidity for 20 minutes using a Gas Tiger6000 apparatus, the hydrogen sulfide generation was measured to be below 310ppm.

15. A method for manufacturing a solid electrolyte, comprising: Step S1: Prepare lithium raw materials, phosphorus sulfide raw materials, transition metal raw materials and halogen element raw materials, and crush and mix them. as well as Step S2 involves calcining the product from step S1 at a temperature range of 300°C to 600°C. The transition metal raw material is any one or more metal compounds selected from transition metal elements with an ionic radius of 0.4 Å or more and 1.0 Å or less and a sulfur dissociation energy of 0.5 eV or more.

16. The method for manufacturing a solid electrolyte according to claim 15, wherein, The transition metal raw material is any one or more metal compounds selected from Co, Ni, Nb, and Mg.

17. The method for manufacturing a solid electrolyte according to claim 16, wherein, The transition metal raw material is any one or more divalent metal halides selected from Co, Ni, Nb, and Mg.

18. The method for manufacturing a solid electrolyte according to claim 15, wherein, Step S2 is performed for more than 4 hours but less than 8 hours.

19. The method for manufacturing a solid electrolyte according to claim 15, wherein, Step S2 is performed in a calcining furnace filled with inert gas.

20. An all-solid-state battery comprising a solid electrolyte according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Solid electrolyte and lithium battery including the same

    US10446872B2